The evolution of surface magnetic fields in young solar-type stars II: the early main sequence (250–650 Myr). Issue 4 (24th November 2017) - Folsom, C P; Bouvier, J; Petit, P; Lèbre, A; Amard, L; Palacios, A; Morin, J; Donati, J-F; Vidotto, A A
Abstract: There is a large change in surface rotation rates of sun-like stars on the pre-main sequence and early main sequence. Since these stars have dynamo-driven magnetic fields, this implies a strong evolution of their magnetic properties over this time period. The spin-down of these stars is controlled by interactions between stellar and magnetic fields, thus magnetic evolution in turn plays an important role in rotational evolution. We present here the second part of a study investigating the evolution of large-scale surface magnetic fields in this critical time period. We observed stars in open clusters and stellar associations with known ages between 120 and 650 Myr, and used spectropolarimetry and Zeeman Doppler Imaging to characterize their large-scale magnetic field strength and geometry. We report 15 stars with magnetic detections here. These stars have masses from 0.8 to 0.95 M⊙, rotation periods from 0.326 to 10.6 d, and we find large-scale magnetic field strengths from 8.5 to 195 G with a wide range of geometries. We find a clear trend towards decreasing magnetic field strength with age, and a power law decrease in magnetic field strength with Rossby number. There is some tentative evidence for saturation of the large-scale magnetic field strength at Rossby numbers below 0.1, although the saturation point is not yet well defined. Comparing to younger classical T Tauri stars, we support the hypothesis that differences in internal structure produce large differences in observed magnetic fields, however for weak-lined T Tauri stars this is less clear.